2009
DOI: 10.1109/tpwrs.2009.2016534
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Network Equivalents for Voltage Optimization in Multi-Area Power Systems

Abstract: Abstract-The paper addresses the problem of decentralized optimization for a power system partitioned into several areas controlled by different transmission system operators (TSOs). The optimization variables are the settings for taps, generators' voltages and compensators', and the objective function is either based on the minimization of reactive power support, the minimization of active power losses, or a combination of both criteria. We suppose that each TSO assumes an external network equivalent for its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 19 publications
0
47
0
Order By: Relevance
“…The selected threshold ( ) for the stop criteria expressed in the expression (17) is 10 −6 . The convergence of this method will be demonstrated by means of empirical methods [26]- [31]. The evolution of the error with respect to the time, the number of iterations and other parameters described in the following paragraphs have been analyzed for a large number of test batteries.…”
Section: B Analysis Of the Algorithm Behaviour In Large Networkmentioning
confidence: 99%
“…The selected threshold ( ) for the stop criteria expressed in the expression (17) is 10 −6 . The convergence of this method will be demonstrated by means of empirical methods [26]- [31]. The evolution of the error with respect to the time, the number of iterations and other parameters described in the following paragraphs have been analyzed for a large number of test batteries.…”
Section: B Analysis Of the Algorithm Behaviour In Large Networkmentioning
confidence: 99%
“…While different types of network equivalents are possible, reference [14] shows that modeling the external network with a constant active and reactive power injection at every point of interconnection yields close to optimal performance even if the TSOs' control actions are not coordinated by a centralized authority.…”
Section: Improved Coordinationmentioning
confidence: 99%
“…In particular, Reference [14] presents a decentralized scheme for reactive power scheduling, where the TSOs concurrently schedule long-term voltage settings within their own control area, while representing the neighboring areas with external network equivalents whose parameters are fitted based on local measurements only. Previous papers [14], [15] have shown that such a coordination scheme could lead to close to optimal settings in the context of small-scale power system models. Furthermore, this promising scheme could be easily implemented on a real power system as it involves few departures from the current practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, ad-hoc decentralized control schemes have been proposed, as in [5], [6] for example. On the other hand, efforts have been made to create higher-level entities, which would be in charge of coordinating operation over very large geographical areas.…”
Section: Introductionmentioning
confidence: 99%